Acceleration of periosteal bone formation by human basic fibroblast growth factor containing a collagen‐binding domain from Clostridium histolyticum collagenase. Issue 6 (24th June 2013) - Uchida, Kentaro; Matsushita, Osamu; Naruse, Kouji; Mima, Takehiko; Nishi, Nozomu; Hattori, Shunji; Ogura, Takayuki; Inoue, Gen; Tanaka, Keisuke; Takaso, Masashi
Abstract Basic fibroblast growth factor 2 (bFGF) is a potent mitogen for mesenchymal cells, and the local application of recombinant bFGF accelerates bone union and defect repair. However, repeated dosing is required for sustained therapeutic effect as the efficacy of bFGF decreases rapidly following its diffusion from bone defect sites. Here, we attempted to develop a collagen‐based bone formation system using a fusion protein (collagen binding‐bFGF, CB‐bFGF) consisting of bFGF and the collagen‐binding domain (CBD) of Clostridium histolyticum collagenase. The addition of the CBD to bFGF did not modify its native biological activity, as shown by the capacity of the fusion protein to promote the in vitro proliferation of periosteal mesenchymal cells. The affinity of the fusion protein towards collagen and demineralized bone matrix (DBM) was also confirmed by collagen‐binding assays. Moreover, in vivo periosteal bone formation assays showed that the combination of CB‐bFGF with a collagen sheet induced periosteal bone formation at protein concentrations lower than those required for bFGF alone. In addition, grafts of DBM loaded with CB‐bFGF accelerated new bone formation in rat femurs compared to the same concentration of bFGF administered alone. Taken together, these properties suggest that the CB‐bFGF/collagen composite is a promising material for bone repair in the clinical setting. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1737–1743, 2014.